Effect of Co on microstructure transformation and refinement mechanism of undercooled Cu-Ni Alloy - Hsien, Willey Liew Yun; AN Hongen; Nancy Julius Siambun; Bih-Lii Chuab (Springer Nature, 2023)
Both Cu60Ni38Co2 and Cu60Ni40 alloy were naturally cooled after rapid solidification from the liquid phase. The transformation law of the microstructure characteristics of the rapidly solidified alloy with the change of undercooling (DT) was systematically studied. It was found that the two alloys experienced the same transformation process. The refinement structures under different undercoolings were characterized by electron backscatter diffraction (EBSD). The experimental results show that the characteristics of the refinement structure of the two alloys with low undercooling are the same, whereas, the characteristics of the refinement structure with high undercooling are opposite. The transmission electron microscope (TEM) results of Cu60Ni38Co2 alloy show that the dislocation network density of low undercooled microstructure is lower than that of high undercooled microstructure. By combining EBSD and TEM, it can be confirmed that the dendrite remelting fracture is the reason for the refinement of the low undercooled structure, while the high undercooled structure is refined due to recrystallization.